A New Species of Calamus from Western Ghats - Fernandez, R. R.; Dey, A. C. (Indian Forester, 1970)
The article reports the discovery of a new species, namely Calamus nagbettai R.R. Fernandez and A.C. Dey. It has been described and illustrated with photographs.